Significant Acute Response of Brain-Derived Neurotrophic Factor Following a Session of Extreme Conditioning Program Is Correlated With Volume of Specific Exercise Training in Trained Men - Pereira, Emy S.; Krause Neto, Walter; Calefi, Atilio S.; Georgetti, Mariana; Guerreiro, Larissa; Zocoler, Cesar A. S.; Gama, Eliane F. (Frontiers in Physiology, 2018)
Several studies have demonstrated an acute and chronic increase of brain-derived neurotrophic factor (BDNF) in relation to different types of physical exercise. Currently, many individuals seek physical training strategies that present different types of stimulation and volume / intensity. Thus, the extreme conditioning methodology has gained great notoriety in the scientific and non-scientific environment. Knowing that BDNF values increase in an effort-dependent manner, it is necessary to study the effects of this strategy on BDNF levels. This study aimed to evaluate the acute response of BDNF in trained men submitted to an extreme conditioning program session (ECP). Ten volunteers underwent an acute ECP session using the "as many reps as possible" (WOD-AMRAP) method, including 3 types of exercise (clean, wall ball and double or single-unders) for 9 minutes. BDNF was measured in the plasma, being collected baseline and immediately after the session. Total load of the clean exercise was 5 times greater than wall ball exercise (p <0.05; 2096.1 ± 387.4 kg vs 415.8 ± 81.03 kg), which influenced little in the total load (p <0.05, 2511.9 ± 358.52 kg) used. For the total volume, practitioners averaged 1.7 times more repetitions in the wall ball exercise compared to clean (46.2 ± 9 vs 29.5 ± 3.8 repetitions). The volunteers averaged 75.7 ± 12.6 double-unders repetitions, bringing the total volume of training to 151.4 ± 23.7 repetitions. Regarding the BDNF values, there was a significant difference (p = 0.05) between the pre versus post moments (11209.85 ± 1270.4 vs 12132.96 ± 1441.93 pg / ml). Effect size for this change as moderate (ES=0.79). We found a positive correlation between total volume of clean exercise and delta BDNF values (p = 0.049). In conclusion, a single extreme conditioning session, through the practice of the WOD-AMRAP method, is capable of increasing the acute concentrations of plasma BDNF. In practical terms, we may suggest that future studies evaluate the effect of ECP as a strategy in the treatment of disorders associated with central degenerative changes.